Performance enhancement of photovoltaic/thermal collector semicircle absorber tubes using nanofluid and NPCM - Maseer M.M.; Ismail F.B.; Kazem H.A.; Hachim D.M.; Al-Gburi K.A.H.; Chaichan M.T. (Elsevier Ltd, 2025)
This experimental measurement examines Photovoltaic/Thermal (PVT) systems with semicircle absorber tubes, focusing on the impact of nanoparticle-enhanced phase change material (NPCM). Four PVT systems are analyzed, all using a standard PV module: a. PVT1: cooled by water; b. PVT2: cooled by water and NPCM; c. PVT3: cooled by nanofluid; d. PVT4: cooled by nanofluid and NPCM.The research evaluates their thermal, electrical, and overall performance and efficiencies at volumetric flow rates of 1?5 LPM under harsh outdoor conditions. The results reveal that the PVT4 system demonstrates the highest efficiency. At a volumetric flow rate of 5 LPM and a surrounding temperature of 47.94 C, it achieves electrical, thermal, and total efficiencies of 12.70 %, 78.99 %, and 91.83 %, respectively. By enhancing the heat transfer between nanofluids and NPCMs, system cooling is enhanced and thermal efficiency is greatly increased. Additionally, the use of such systems notably reduced the surface temperature, exhibiting a decrease of about 35.09 % compared to the standard PV module while the use of nanofluid cooling only without NPCM caused a reduction of 29.93 % compared to the PV module. Importantly, the PVT4 setup outperforms the unenhanced PV module (PVT3) in overall efficiency by 14.04 %. In this study, PV modules are cooled by a heat exchanger made up of semicircular tubes attached to their backs. The study confirms that a PCM enhanced with nanoparticles performs well in the PVT system when semicircular absorption tubes are used. A significant reduction in surface temperatures is achieved with the use of this heat exchanger, resulting in remarkable thermal efficiency. As a result of this cooling effect, the PV module is more efficient than a traditional solar module in terms of electrical output. This type of system is likely to influence the development of more convenient and efficient solar energy systems. It is possible to use the heat absorbed by PV modules in other ways as well. ? 2024 Elsevier Ltd